2002
DOI: 10.2118/02-11-das
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Formation Damage Mechanisms Causing a Reduction in the Productivity and Injectivity of Oil and Gas Producing Formations

Abstract: Introduction Formation damage is a hot topic these days-with justifiable reason, as more operating companies move to the exploitation of more and more challenging oil and gas reservoirs in tighter, deeper, and more depleted conditions. Disappointing production or injection results from an oil or gas well can be related to a number of factors which may be difficult to diagnose. Some of these may center about poor inherent natural reservoir quality characteristics, others about mechanical consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(70 citation statements)
references
References 0 publications
1
50
0
11
Order By: Relevance
“…These results are in excellent agreement with previous studies reported in the literature for asphaltene adsorption from oil solutions with different precipitants onto different solid surfaces, such as hydrophilic and hydrophobic silica particles, 68 clay minerals (like kaolinite, illite, montmorillonite and mineral oil reservoir rocks), 69 coated quartz crystals 70 and metals. 54,71 It is well known that by adding an asphaltene precipitant to a heavy oil solution, the solubility of asphaltenes will decrease and hence asphaltene aggregation and self-association will be enhanced.…”
Section: N-c7 Asphaltenes Adsorption Isothermsmentioning
confidence: 99%
“…These results are in excellent agreement with previous studies reported in the literature for asphaltene adsorption from oil solutions with different precipitants onto different solid surfaces, such as hydrophilic and hydrophobic silica particles, 68 clay minerals (like kaolinite, illite, montmorillonite and mineral oil reservoir rocks), 69 coated quartz crystals 70 and metals. 54,71 It is well known that by adding an asphaltene precipitant to a heavy oil solution, the solubility of asphaltenes will decrease and hence asphaltene aggregation and self-association will be enhanced.…”
Section: N-c7 Asphaltenes Adsorption Isothermsmentioning
confidence: 99%
“…Expandable clays can swell 600 to 1000 times their original volume after exposure to incompatible fluids, expanding to plug pores and pore throats, reducing permeability of formations drastically and leading to formation damage (Brian, D., 2004, Erwom, M.D., 2003, Bennion, D., 2002. The fines generated during swelling can also migrate and plug at pore throats, reducing permeability further.…”
Section: Formation Sensitivitymentioning
confidence: 99%
“…When the pore fluid conditions are favorable for phase entrapment and immobilization, a phase can be trapped inside another phase (Bennion, 2002).…”
Section: Entrapment Shock-critical Phase Entrapment Condition (Cpec)mentioning
confidence: 99%
“…However, other substances, such as drilling mud, hydraulic fracturing fluids, cement, various debris, may also invade the reservoir formation as a result of the practices required for petroleum recovery from subsurface reservoirs. Examples of these include the materials used for fluid loss control, mud weighting, and pore blocking/bridging, particulates present in injection water, drill cuttings, and various corrosion products (Bennion andThomas, 1994, Bennion, 2002). Ordinarily, the mineral matter loosely attached at the pore surface is not free to interact with the other minerals.…”
Section: Introductionmentioning
confidence: 99%